Islamic School Culture dan Upaya Menanamkan Nilai-Nilai Religious di SMP Islamic Qon Gresik - Saeful Anam; Muhammad Sidiq Jaelani (Proceedings of Annual Conference for Muslim Scholars, 2018)
This article discusses about the Islamic school culture as an effort to instill religious values ​​in school institutions. Where the demand to create a good environmental setting is a necessity in the teaching of Islam, this is aimed not only as an effort to provide knowledge, experience as well as exemplary in religion directly on the learners, so that in life, learners are able to interact well. This research was conducted at SMP Islamic Qon Gresik, a public school institution that has an academic peculiarity with its religious content in it. The results of this study indicate that learners who are familiarized to do good in the process with the given environment setting, then by itself they will get used to doing good without any compulsion from other. The moral development of children in the modern era today requires a role model and direction to learn to be good, without the role model and direction then he will be a blind person to religious values, and finally juvenile delinquency will spread and become the worries of society and become public waste